Multiplicative filtering in the linear canonical transform domain. Issue 2 (1st April 2016) - Goel, Navdeep; Singh, Kulbir; Saxena, Rajiv; Singh, Ashutosh Kumar
Abstract : As a generalisation of fractional Fourier transform, Fresnel transform and Fourier transform, the linear canonical transform (LCT) is a four parameter class of integral transform and has been used in many fields of optics and signal processing. In this study, the authors present a model of multiplicative filtering for the band‐limited signals in the LCT domain by using the convolution theorem given in the literature. Finally, practical applications of filtering in LCT domain are discussed based on the presented model of multiplicative filtering and results are compared with that of frequency domain filtering and fractional domain filtering. It is found from the simulation results that mean square error is minimum for different values of signal‐to‐noise ratio in case of LCT domain filtering.